Investigation of an alternative testing protocol to determine the shear strength of bamboo parallel to the grain - Luisa Cantos, Gabrielle; F. Lopez, Luis; M. de Jesus, Richard; Salzer, Corinna; E. O. Garciano, Lessandro (Maderas. Ciencia y Tecnología, 2019)
The common testing protocol to determine the shear strength of bamboo parallel to grain is ISO 22157. However, widely documented limitations of this test procedure calls for an alternative testing protocol. This study compared ISO 22157 (TP1) and 2 alternative testing protocols proposed by Base Bahay (TP2a and 2b) in determining shear strength of bamboo parallel to grain. The study used a local bamboo known as “kawayang tinik” (Bambusa blumeana). Results showed that TP1 produced more pure shear failures at 65% compared to TP2a and TP2b at 55% each. Shear strength values between the three methods were not significantly different, although, TP2b resulted in the lowest coefficient of variation at 18%. Also, TP2b was found to be the most effective in terms of specimen preparation, ease of assembly of testing equipment, and low variability in data.